2021
DOI: 10.1093/nar/gkab132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of permissive amber suppression sites for efficient non-canonical amino acid incorporation in mammalian cells

Abstract: The genetic code of mammalian cells can be expanded to allow the incorporation of non-canonical amino acids (ncAAs) by suppressing in-frame amber stop codons (UAG) with an orthogonal pyrrolysyl-tRNA synthetase (PylRS)/tRNAPylCUA (PylT) pair. However, the feasibility of this approach is substantially hampered by unpredictable variations in incorporation efficiencies at different stop codon positions within target proteins. Here, we apply a proteomics-based approach to quantify ncAA incorporation rates at hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 114 publications
2
47
0
Order By: Relevance
“…ncAA incorporation into endogenous stop codons is thought to be disfavored by strong termination signals associated with terminal stop codons and quality control mechanisms that mitigate aberrantly elongated protein products. [32][33][34] While this result hinted that the proteome of CTL07-II-AS hiPSCs was not collaterally affected by the amber suppression machinery, we also confirmed that expression of the pluripotency marker OCT4 was not affected by 24 h incubation with 0.2 mM CpK (Figure S2). Nevertheless, we note that applications of genetic code expansion in hiPSCs or derived cell lines need to consider inference from off-target effects of amber suppression activity, and it will be important to optimize concentration and incubation time of ncAA to minimize such effects.…”
Section: Efficient and Selective Non-canonical Amino Acid Incorporation In Hipscssupporting
confidence: 67%
“…ncAA incorporation into endogenous stop codons is thought to be disfavored by strong termination signals associated with terminal stop codons and quality control mechanisms that mitigate aberrantly elongated protein products. [32][33][34] While this result hinted that the proteome of CTL07-II-AS hiPSCs was not collaterally affected by the amber suppression machinery, we also confirmed that expression of the pluripotency marker OCT4 was not affected by 24 h incubation with 0.2 mM CpK (Figure S2). Nevertheless, we note that applications of genetic code expansion in hiPSCs or derived cell lines need to consider inference from off-target effects of amber suppression activity, and it will be important to optimize concentration and incubation time of ncAA to minimize such effects.…”
Section: Efficient and Selective Non-canonical Amino Acid Incorporation In Hipscssupporting
confidence: 67%
“…Among other factors, the UAA incorporation efficiency depends on the sequence surrounding the TAG amber codon (Bartoschek et al, 2021). We used a recently developed tool (Bartoschek et al, 2021) to predict the UAA incorporation efficiency rate in the three remaining amber mutants. The iPASS (identification of p ermissive a mber s ites for s uppression) score was higher for NF186 K680TAG -HA (1.83) than for NF186 K519TAG -HA (1.61) and NF186 K604TAG -HA (1.63).…”
Section: Resultsmentioning
confidence: 99%
“…Our study highlights the importance of anticodon base modification in the context of hydrogen bonding. It is well-known that the yield of modified protein depends on the UAG site selection, called mRNA context effect 41 . One report suggested that RF1 interactions during translation depend on mRNA sequence context, and contributed approximately half of the observed difference in reassignment efficiency 42 .…”
Section: Effect Of Trna Analog On Decoding Two Uag Sitesmentioning
confidence: 99%